Academic performance and professional goals of adolescent Filipino children of migrant mothers from a sub-urban setting in the Philippines - Hernandez, Lynne Grace C.
Migration in the Philippines is a viable option for employment given the Philippine economic situation.Female migration which is consistently on the rise is seen to affect the Filipino family as well as its individual members. There are differing findings on its effect on the migrant mother's child. This study seeks to find out the academic performance and future professional goals of adolescent children of migrant mothers in Rizal, where female migration is highest in the Philippines.Children of migrant mothers were identified through a survey among the three schools in Taytay, Antipolo and Angono, Rizal from 2008 to 2010. In-depth interviews were conducted with thirty children of migrant mothers, after which General Weighted Averages (GWA) and grades in conduct were collected.Results of statistical analysis made through ANOVA and T-Tests show that mean GWAs and grades in conduct of children of migrant mothers are not significantly different from that of the population. However, among children of migrant mothers, there is a significant difference between males and females, indicating that adolescent male children of migrant mothers may be more affected by the mother's migration. Feelings of longing and sadness are encountered by all. Economic benefits are acknowledged by majority. Detriments brought by mother's migration is lack of care, attention, guidance and monitoring in studies while benefit for others is the development of responsibility and independence, diligence, skill and self-control and strength, determination and courage. Children of migrant mothers would like to pursue careers in the Hotels and Restaurants industry, Health Profession and Media. Most of the adolescents based choice on personal preferences, appropriateness to skill and desire to help others. More than half would like to work abroad. With the family as a network of social exchanges, choices made by children on behaviors regarding their academic performance and professional goals are made with costs and benefits as consideration. Further studies on the situation of left behind husbands of migrant mothers, differential effect of maternal migration on male and female adolescent children and parenting of migrant mothers specific to children's gender are recommended. Attention to the preparation, adjustment and coping of left-behind family members of migrant mothers should be emphasized. It is therefore recommended that programs addressing role adjustments, strong parent-child relationships and peer relations monitoring be provided by other institutions (educational, religious and governmental).